(untitled) (Research, Society and Development, 2021)
Lesions on the face, affected by domestic animals, are among the most common types of trauma, particularly in children. The injuries caused in this region, can generate a series of morbidities such as important tissue loss, infections, death in more severe cases, in addition to irreversible scars when the wound is liable to repair, therefore, post trauma care should aim, at minimization of healing, in addition to functionality, seeking as much aesthetics as possible. A thorough initial clinical evaluation is essential, and, from there, the definition of the most appropriate treatment for the specific case is essential to reduce the risk of more serious infections and, consequently, the successful treatment of these patients. This paper aims to report a clinical case of a child victim of animal bite with the presence of extensive laceration in the frontal region, attended by the FOA Unesp Oral and Traumatology Maxillofacial Surgery service, treated by primary repair and prophylactic antibiotic therapy, in which the result of the treatment was considered satisfactory with no infection.